Stress, well-being, and performance in sport - Arnold, Rachel; Fletcher, David (New York Routledge, 2021)
"Stress, Well-Being, and Performance in Sport provides the first comprehensive and contemporary overview of stress in sport and its implications on performance and well-being. It explores how athletes', coaches, and support staff's performance can be enhanced while simultaneously optimizing their well-being in contemporary sport. Divided into four sections following the stress process, Stress, Well-Being, and Performance in Sport covers key topics including: Appraising and coping with stress in sport Responses to and outcomes of stress in sport, Moderators of the stress process in sport, Stress management to promote thriving in sport Bringing together theory and practice, each chapter discusses conceptual and theoretical issues, current research, and innovative practical implications. Written by scholars around the globe, Stress, Well-being, and Performance offers an international perspective. It is important reading for students of sport psychology as well as coaches, athletes, and support staff"--
Stressors, hassles, and adversity / Rachel Arnold and David Fletcher -- Cognitive appraisals / Faye F. Didymus and Marc V. Jones -- Coping / Katherine A. Tamminen -- Emotions Christopher R.D. Wagstaff, and Katherine A. Tamminen -- Attention and visuomotor performance under pressure / Lee J. Moore, Samuel J. Vine, and Mark R. Wilson -- Well-being and quality of life / Carolina Lundqvist -- Burnout / J.D. DeFreese and Robert C. Eklund -- Mental health / Simon Rice, Courtney C. Walton, Kate Gwyther, and Rosemary Purcell -- Stress-related growth and resilience / David Fletcher -- Personality / Sylvain Laborde, Sinikka Heisler, and Emma Mosley -- Social support / Paul Freeman -- Stress and pressure training / David Fletcher and Rachel Arnold -- Thriving / Daniel J. Brown, Michael Passaportis, and Kate Hays -- Duties of care and welfare practices / Emma Kavanagh, Daniel Rhind, and Genevieve Gordon-Thomson -- Conclusion / Rachel Arnold and David Fletcher -- Epilogue / Cary Cooper.
Includes bibliographical references and index.
Keywords: Sports--Psychological aspects; Stress (Psychology); Athletes--Mental health; Athletes--Training of